Tax Implications of Brexit – The Road Ahead - Kanwal D. P. Singh, Dr. (Kathmandu School of Law Review, 2017)
On 23rd June 2016, the people of United Kingdom voted to exit from the European Union. This exit impacts the economies of the UK and EU both in many ways. Numerous changes in taxation structure, tariffs, business methodology will be seen. These tax implications and the impact of the exit decision on economy and business are unclear. This article analyses the legal implications and the process of exit to be followed after the referendum and the various strategies to proceed and their legal standing are discussed. The main issues that the economies of UK and EU shall face are discussed in the article. It also discusses the potential economic changes that might occur along with the impact of Brexit on corporate tax structure, social security, trade and other areas respectively.